Struktur Frasa dalam Buku Kumpulan Puisi Aku Ini Binatang Jalang Karya Chairil Anwar - M. Abdullah; Ermawati Sulaiman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The Indonesian phrase structure is a group of words that are a functional part of a long speech. In print media, such as books, there are words that are arranged using a phrase structure. The author chose the object of Chairil Anwar's poetry collection because in the poem there are poems composed of phrases. The purpose of this study was to identify and analyze nominal phrases, verbal phrases, adjective phrases, prepositional phrases and numeral phrases contained in the book collection of poems Aku Ini Binatang Jalang by Chairil Anwar. The theory used in this study refers to various theories put forward by Sulistyowati (2013), Ramlan (2014), as well as other supporting theories. The method used is descriptive method. The approach used in this research is a qualitative approach. This type of research is a library. Data collection techniques using documentation techniques and hermeneutic techniques. Based on the research conducted, it can be concluded that 1) the nominal phrase structure consists of N1 + N2, N + V, V + N, Adj + N, N + Adj, Adv + N, and N + Pron. An example of a nominal phrase structure is up (N1) + dust (N2). 2) the structure of the verbal phrase consists of V1 + V2, V + N, Adv + V. An example of a verbal phrase structure is piercing (V) + heart (N). 3) the structure of the adjective phrase consists of Adj + N, N + Adj, Adj + V, Adj + V, V + Adj, Adv + Adj, Adj + bound form. An example of an adjective phrase structure is melodious (Adj) + song (N). 4) the prepositional phrase structure consists of P + N, P + V.